Replication study: androgen receptor splice variants determine taxane sensitivity in prostate cancer - Shan,Xiaochuan; Danet-Desnoyers,Gwenn; Aird,Fraser; Kandela,Irawati; Tsui,Rachel; Perfito,Nicole; Iorns,Elizabeth (PeerJ, 2018)
In 2015, as part of the Prostate Cancer Foundation–Movember Foundation Reproducibility Initiative, we published a Registered Report (Shan et al., 2015) that described how we intended to replicate selected experiments from the paper “Androgen Receptor Splice Variants Determine Taxane Sensitivity in Prostate Cancer” (Thadani-Mulero et al., 2014). Here we report the results of those experiments. Growth of tumor xenografts from two prostate cancer xenograft lines, LuCaP 86.2, which expresses wild-type androgen receptor (AR) and AR variant 567, and LuCaP 23.1, which expresses wild-type AR and AR variant 7, were not affected by docetaxel treatment. The LuCaP 23.1 tumor xenografts grew slower than in the original study. This result is different from the original study, which reported significant reduction of tumor growth in the LuCaP 86.2. Furthermore, we were unable to detect ARv7 in the LuCaP 23.1, although we used the antibody as stated in the original study and ensured that it was detecting ARv7 via a known positive control (22rv1, Hörnberg et al., 2011). Finally, we report a meta-analysis of the result.
Keywords: PCFMFRI; Androgen receptor variants; Castration resistant prostate cancer; Methodology; Docetaxel